2007
DOI: 10.1073/pnas.0708866104
|View full text |Cite
|
Sign up to set email alerts
|

Human capping enzyme promotes formation of transcriptional R loops in vitro

Abstract: Cap formation is the first step of pre-mRNA processing in eukaryotic cells. Immediately after transcription initiation, capping enzyme (CE) is recruited to RNA polymerase II (Pol II) by the phosphorylated carboxyl-terminal domain of the Pol II largest subunit (CTD), allowing cotranscriptional capping of the nascent premRNA. Recent studies have indicated that CE affects transcription elongation and have suggested a checkpoint model in which cotranscriptional capping is a necessary step for the early phase of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…The GST-eIF4E plasmid used for the capping assays was the kind gift of J. Pelletier (39). pBH161-CTD, the vector used for bacterial expression of T7CTD, was a gift of J. Manley (40). pBH161-T7 bacterial expression vector was constructed by digesting pBH161-CTD with XhoI and religating the vector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GST-eIF4E plasmid used for the capping assays was the kind gift of J. Pelletier (39). pBH161-CTD, the vector used for bacterial expression of T7CTD, was a gift of J. Manley (40). pBH161-T7 bacterial expression vector was constructed by digesting pBH161-CTD with XhoI and religating the vector.…”
Section: Methodsmentioning
confidence: 99%
“…Induction of protein expression and subsequent protein purification were carried out as described previously (40). The CTD was cloned as an amino-terminal fusion, as it is well established that T7 RNAP does not tolerate carboxyl-terminal extensions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S14), but the small number of genes is not enough to establish a significant association. A recent study suggests that, on top of the higher stability of RNA/DNA compared with the DNA/DNA structure, a capping enzyme can promote formation of transcriptional R-loops in vitro (Kaneko et al 2007). Since the formation of a cap is a necessary process at early stages of transcription, this finding implies that R-loops are indeed found at higher frequencies near the TSS than in the rest of the transcript.…”
Section: Localization Of Mutationsmentioning
confidence: 99%
“…29 Since R-loops can negatively regulate the stability and processivity of elongating RNAP II, it has been suggested that capping enzyme-mediated R-loop formation modulates RNAP II dynamics at promoter-proximal pause sites, providing a kinetic "window of opportunity". 19,29 The CAG repeat within the HTT gene is close to TSS (< 200 nucleotides). It is therefore possible that the proximity between promoter-proximal region and CAG repeats provides a particular environment favoring stable R-loop formation at the HD locus.…”
Section: Does Rnap II Dynamics At Proximal-promoters Underlie Tissue-mentioning
confidence: 99%